2014
DOI: 10.1364/oe.22.004152
|View full text |Cite
|
Sign up to set email alerts
|

Supercontinuum generation in highly nonlinear fibers using amplified noise-like optical pulses

Abstract: Supercontinuum generation in a highly nonlinear fiber pumped by noise-like pulses from an erbium-doped fiber ring laser is investigated. To generate ultrabroad spectra, a fiber amplifier is used to boost the power launched into the highly nonlinear fiber. After amplification, not only the average power of the noise-like pulses is enhanced but the spectrum of the pulses is also broadened due to nonlinear effects in the fiber amplifier. This leads to a reduction of the peak duration in their autocorrelation trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…SC light can be generated using different methods and from different sources including continuous wave (CW) [32] or pulsed sources like short pulses [33], ultra-short pulses [34] and even NLPs [25,26,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…SC light can be generated using different methods and from different sources including continuous wave (CW) [32] or pulsed sources like short pulses [33], ultra-short pulses [34] and even NLPs [25,26,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Because the peak output power decreases, nonlinear effects in the cavity are not strong enough to result in wave breaking. The laser operating in this regime can be amplified to serve as a pump to generate a supercontinuum [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, peak power of sub-pulses may far exceed the average peak power of the entire wave packet because of their short duration. It was also established that double-scale pulses feature comparatively high efficiency of non-linear interaction with the propagation medium in harmonic generation [8], Raman conversion [9] or super-continuum generation [10][11][12][13]. We analyse these and other promising applications of double-scale pulses in the following discussion.…”
Section: Applicationsmentioning
confidence: 98%
“…Nevertheless, over recent years, this topic has been rapidly gaining popularity after the observation of double-scale pulses with relatively high energy in ultralong fibre lasers. Active research prompted by this discovery has shown that double-scale pulses may even be preferable in a number of applications, including non-linear frequency conversion, such as harmonic generation [8], Raman conversion [9] or super-continuum generation [10][11][12][13], as well as applications in imaging and sensing systems with high temporal and/or spatial resolution. It was furthermore demonstrated that generation of double-scale pulses in long lasers represents a remarkably multiform phenomenon encompassing many non-linear optical mechanisms, whose interaction may result in the emergence of diverse spatio-temporal coherent structures in laser radiation [14].…”
Section: Introductionmentioning
confidence: 99%